Collaborative Learning and Its Effect on Critical Reading Development in EFL Classes - Rizal, Awaludin; Ridayani, Ridayani; Ais, Amirudin; Hasyim, Irmawaty; Sudirman, Sahrun (English Education Department, 2026)
This study investigates the impact of collaborative learning on the development of critical reading skills in English as a Foreign Language (EFL) class. Thirty-four students in the experimental group were engaged in collaborative learning activities, while thirty-four students in the control group received conventional instruction. Both groups completed pre-tests and post-tests assessing their critical reading abilities. The results demonstrated a significant improvement in the experimental group, with mean scores rising from 65.53 (SD = 5.91) in the pre-test to 89.00 (SD = 4.78) in the post-test. In contrast, the control group exhibited only a modest increase, from a pre-test mean of 64.71 (SD = 5.97) to a post-test mean of 68.62 (SD = 6.12). Statistical analyses, including independent and paired samples t-tests, confirmed that the improvement in the experimental group was significantly greater than in the control group (p < 0.001). These findings suggest that collaborative learning strategies are highly effective in enhancing critical reading skills among EFL learners. The study highlights the importance of interactive and student-centered approaches in language education to foster deeper comprehension and critical thinking in reading